Molecular characterization of CHST11 and its potential role in nacre formation in pearl oyster Pinctada fucata martensii - Qingheng Wang; Chuangye Yang; Ruijuan Hao; Zhe Zheng; Yu Jiao; Xiaodong Du; Yuewen Deng; Ronglian Huang (Electronic Journal of Biotechnology, 2017)
Background: C4ST-1 catalyzes the transfer of sulfate groups in the sulfonation of chondroitin during chondroitin sulfate synthesis. Chondroitin sulfate consists of numerous copies of negatively charged sulfonic acid groups that participate in the nucleation process of biomineralization. In the present study, we obtained two CHST11 genes (PmCHST11a and PmCHST11b) which encoded the C4ST-1 and explored the functions of these genes in the synthesis of chondroitin sulfate and in the formation of the nacreous layer of shells. Results: Both PmCHST11a and PmCHST11b had a sulfotransferase-2 domain, a signal peptide and a transmembrane domain. These properties indicated that these genes localize in the Golgi apparatus. Real-time PCR revealed that both PmCHST11a and PmCHST11b were highly expressed in the central zone of the mantle tissue. Inhibiting PmCHST11a and PmCHST11b via RNA interference significantly decreased the expression levels of these genes in the central zone of the mantle tissue and the concentration of chondroitin sulfate in extrapallial fluid. Moreover, shell nacre crystallized irregularly with a rough surface after RNA interference. Conclusions: This study indicated that PmCHST11a and PmCHST11b are involved in the nacre formation of Pinctada fucata martensii through participating in the synthesis of chondroitin sulfate.